Acceptable temperature steps for occupants moving between air-conditioned main space and naturally ventilated transitional space of building. (September 2020) - Lu, Pin; Li, Jin
Abstract: Transitional spaces occupy large areas in buildings, hence naturally ventilated transitional spaces boast a huge potential of energy saving. However, it is uncertain whether occupants will experience unacceptable temperature step when moving between air-conditioned main spaces and naturally ventilated transitional spaces, particularly considering the impacts of different activity types in the main spaces to the subjective perceptions. A field survey was conducted in a commercial complex in Guangzhou, China in the summer of 2019. Questionnaires were used to collect thermal perception of subjects under different activities, including sitting, 3 km/h walking and 6 km/h walking, in air-conditioned main space when they moving between air-conditioned main space and naturally ventilated transitional space, and instruments were used to record environmental and physiological data. This study identified the average metabolic rates and the 80% acceptable operative temperature step of subjects under aforesaid three activity types. During the spatial transition between air-conditioned space and naturally ventilated space, the acceptable temperature step decreased with the rising of activity intensity in air-conditioned space. In addition, the acceptable temperature step found through field survey in this study was higher than that found through climatic chamber experiments in previous studies. This study facilitates a better understanding of temperature step effect and provides a reference for the passive design of transitional spaces. Highlights: Field survey of thermal responses during spatial transitions between AC & NV space. Acceptable temperature step (ATS) for people under different activities in AC space were identified. ATS decreased with the increase of activity intensity in AC space. ATS was higher in this study (field survey) than previous studies (climatic chamber experiment).